2020
DOI: 10.1038/s41467-020-16951-w
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of spurious transcription initiation in Arabidopsis

Abstract: In plants, epigenetic regulation is critical for silencing transposons and maintaining proper gene expression. However, its impact on the genome-wide transcription initiation landscape remains elusive. By conducting a genome-wide analysis of transcription start sites (TSSs) using cap analysis of gene expression (CAGE) sequencing, we show that thousands of TSSs are exclusively activated in various epigenetic mutants of Arabidopsis thaliana and referred to as cryptic TSSs. Many have not been identified in previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 96 publications
7
48
0
Order By: Relevance
“…All the independent transgenes analyzed produce new antisense transcripts initiating in the first intron. Consistent with this, recent genome-wide measurements of TSSs showed that extensive alternative intragenic transcriptional initiation occurs in Arabidopsis, and this can be affected by cold (Kindgren et al 2018), cotranscriptional RNA degradation (Thieffry et al 2020;Thomas et al 2020), or mutants disrupted in chromatin signaling (Nielsen et al 2019;Le et al 2020). The activation of alternative TSSs significantly influences transcription from nearby TSSs, and thus is important for plant development and adaptation to environmental changes (Kindgren et al 2018;Nielsen et al 2019;Le et al 2020;Thieffry et al 2020;Thomas et al 2020).…”
Section: Discussionmentioning
confidence: 67%
“…All the independent transgenes analyzed produce new antisense transcripts initiating in the first intron. Consistent with this, recent genome-wide measurements of TSSs showed that extensive alternative intragenic transcriptional initiation occurs in Arabidopsis, and this can be affected by cold (Kindgren et al 2018), cotranscriptional RNA degradation (Thieffry et al 2020;Thomas et al 2020), or mutants disrupted in chromatin signaling (Nielsen et al 2019;Le et al 2020). The activation of alternative TSSs significantly influences transcription from nearby TSSs, and thus is important for plant development and adaptation to environmental changes (Kindgren et al 2018;Nielsen et al 2019;Le et al 2020;Thieffry et al 2020;Thomas et al 2020).…”
Section: Discussionmentioning
confidence: 67%
“…However, errors in restricting CMT3 to heterochromatin are inevitable on an evolutionary timescale ( Zhang et al, 2020 ) and recent studies indicate that CMT3-induced methylation of genes precedes gbM ( Wendte et al, 2019 ). Because gbM can be stably maintained over many generations by MET1 and its functional significance is debatable ( Bewick et al, 2016 ; Bewick et al, 2019 ; Choi et al, 2020 ; Coleman-Derr and Zilberman, 2012 ; Le et al, 2020 ; Picard and Gehring, 2017 ; Shahzad et al, 2021 ; Takuno and Gaut, 2013 ; Wendte et al, 2019 ; Williams et al, 2021 ; Zilberman, 2017 ), it cannot be excluded that gbM is merely an evolutionary record of epigenetic collateral damage events that occurred in the past ( Bewick and Schmitz, 2017 ; Bewick et al, 2017 ). Our results suggest that derepressed CMT3 and MET1 both prefer genic regions characterized by increased nucleosome stability ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, errors in restricting CMT3 to heterochromatin are inevitable on an evolutionary timescale (Zhang et al, 2020) and recent studies indicate that CMT3-induced methylation of genes precedes gbM (Wendte et al, 2019). Because gbM can be stably maintained over many generations by MET1 and its functional significance is debatable (Bewick et al, 2016(Bewick et al, , 2019Choi et al, 2019;Coleman-Derr and Zilberman, 2012;Le et al, 2020;Picard and Gehring, 2017;Shahzad et al, 2021;Takuno and Gaut, 2013;Wendte et al, 2019;Williams et al, 2021;Zilberman, 2017), it cannot be excluded that gbM is merely an evolutionary record of epigenetic collateral damage events that occurred in the past . Our results suggest that…”
Section: Discussionmentioning
confidence: 99%